Implementasi Kebijakan Pemilihan Kepala Pemerintahan Kampung serentak di Kota Jayapura - supriyanto supriyanto; Akbar Silo; Untung Muhdiarta; Yusuf Gabriel Maniagasi (JURNAL EKOLOGI BIROKRASI, 2025)
This study aims to analyze the implementation of the simultaneous village head election policy in Jayapura City and to identify the supporting and inhibiting factors affecting its implementation. The research employs a qualitative descriptive approach to examine policy implementation dynamics at the local level. Data were collected through interviews, observations, and document analysis involving government officials, election committees, community leaders, and village communities who were directly involved in the election process. The analysis uses the policy implementation framework of Edwards III, which emphasizes communication, resources, disposition, and bureaucratic structure, combined with Grindle’s approach that highlights policy content and the context of implementation. The findings show that the implementation of the simultaneous village head election policy in Jayapura City has generally been carried out in accordance with existing regulations. The policy implementation is supported by clear regulatory frameworks, strong commitment from the local government, active community participation, and the involvement of customary leaders in maintaining social stability. Effective communication between local government institutions and village-level actors has also improved understanding of election procedures and policy objectives. However, several challenges still influence the effectiveness of policy implementation, including limited administrative capacity of election organizers at the village level, coordination issues among implementing institutions, and the influence of local political dynamics during the election process. Moreover, the strong role of traditional social structures in Papuan communities sometimes requires adjustments between formal democratic procedures and local cultural values. Therefore, strengthening institutional capacity, improving coordination among stakeholders, and integrating local cultural values into governance practices are essential to enhance the effectiveness and sustainability of the simultaneous village head election policy in Jayapura City.